2011
DOI: 10.1007/s00227-011-1798-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence in the high Arctic during the polar night

Abstract: This study examines the composition and activity of the planktonic community during the polar night in the high Arctic Kongsfjord, Svalbard. Our results are the first published evidence of bioluminescence among zooplankton during the Arctic polar night. The observations were collected by a bathyphotometer detecting bioluminescence, integrated into an autonomous underwater vehicle, to determine the concentration and intensity of bioluminescent flashes as a function of time of day and depth. To further understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Most of the meroplankton seasonal occurrence seems to be driven by spring and summer nutrient availability in the water column. However, our settlement experiment recorded recruitment also in the winter and thus further stresses that winter ecology in the high Arctic is a major gap in our current knowledge and understanding of Arctic marine ecosystems (e.g., Berge et al 2009Berge et al , 2012. Additionally, these results reveal strategies in the life history of Arctic benthic organisms.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Most of the meroplankton seasonal occurrence seems to be driven by spring and summer nutrient availability in the water column. However, our settlement experiment recorded recruitment also in the winter and thus further stresses that winter ecology in the high Arctic is a major gap in our current knowledge and understanding of Arctic marine ecosystems (e.g., Berge et al 2009Berge et al , 2012. Additionally, these results reveal strategies in the life history of Arctic benthic organisms.…”
Section: Discussionmentioning
confidence: 61%
“…Despite the enormous pressure on polar systems caused by factors which include increasing seawater temperature and the disappearance of the permanent ice, we still do not have sufficient knowledge about the current state of a number of biological processes (see e.g., Berge et al 2012). Some examples are the intra-annual seasonality of meroplankton occurrence, timing of benthic organisms' recruitment, and the factors driving their abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the prey items such as Thysanoessa spp. (krill) are known to be bioluminescent [37], which might act as a cue for detecting these organisms in the dark [37][38][39]. However, there are clearly other search mechanisms that need to be investigated, such as acoustic and/or tactile mechanisms, as suggested for cormorants and petrels [36,40].…”
Section: Seabird and Fish Communitiesmentioning
confidence: 97%
“…Most deep-sea animals and many bacteria are bioluminescent and high levels of bioluminescence have been detected in the deep Mediterranean for periods lasting several months (Tamburini et al, 2013). This process also occurs in the Arctic, but the reported photic levels (Berge et al, 2012) are lower than those observed in the Mediterranean. When a full Moon occurs at high latitudes, it provides light over prolonged periods.…”
Section: Seasonal Trends In Pr Presence and Expressionmentioning
confidence: 99%